Assessing the Implementation of Statistical Process Control in Food Industries: An Empirical Study from a Developing Country Context - Mohammad Kanan; Ali Jebreen; Yahya Saleh; Ahmed A. Zaid; Ramiz Assaf; Weam Tunsi; Abdalmuttaleb Al-Sartawi (Operational Research in Engineering Sciences: Theory and Applications, 2023)
This study delves into an examination of the correlation between the utilization and integration of seven widely recognized Statistical Process Control (SPC) tools, namely flow charts, check sheets, Pareto charts, cause-and-effect diagrams, scatter charts, histograms, and control charts. These tools are represented by variable Statistical Methods (SM) training. The research also investigates the relationship between these SPC tools and five critical success factors within the context of Palestinian food companies. These factors encompass Managerial Actions (MA), the Process Approach (PA), Decision-Making (DM), Audit and Review (AR) of SPC practices, and Quality Obstacles (QO) related to their implementation. The research adopts a quantitative methodology, wherein pertinent data is gathered through the administration of a questionnaire to 75 quality managers employed within Palestinian food companies. Subsequently, the data is subjected to analysis via the utilization of partial least squares structural equation modeling (PLS-SEM). The study's findings indicate that approximately 50% of the selected food companies have adopted SPC tools. Furthermore, the research has identified connections among the critical success factors that contribute to improving the implementation of SPC tools within the food industry. Concretely, the results demonstrate that MA, a PA, DM, and QO exert substantial influences on SPC implementation SM in Palestinian food enterprises. In contrast, neither AR nor DM exhibit significant impacts on SPC implementation. The study's findings emphasize the critical role of implementing SPC tools in reducing the occurrence of defective food products. Senior management in the food industry must take proactive measures to address and eliminate impediments to the integration of SPC tools. This research provides empirical insights to enhance SPC implementation in the food industry, focusing on critical success factors like MA, the PA, DM, and QO. Ultimately, SPC integration positively enhances the effectiveness of quality improvement initiatives in the food industry, leading to increased competitiveness and improved customer satisfaction. Despite the prevalent utilization of SPC within the manufacturing industry, the successful application of SPC tools in the food sector remains inadequately explored in the scholarly domain. Existing studies have often limited their scope to a subset of SPC tool applications. Therefore, this study makes a noteworthy contribution to the extant literature by presenting the outcomes of a distinctive investigation conducted within a developing-country context. It offers a comprehensive evaluation of SPC tool implementation in the food industry and scrutinizes the essential critical success factors associated with this process. Notably, to the best of the authors' knowledge, this study represents the inaugural endeavor of its kind in the Palestinian context.